Microbial Load in Fore-milk and Total Milk of Iraqi Local Goat Breed - AL-Hubaety, Arif Kassim; Mate, Rimon Waadullah (Sulaimani Journal for Pure and Applied Sciences, 2014)
The current study was carried out on ten local goat breed belong to a private farmers in Bashika city, 20 km north east of Mosul province. The aim of this study was to evaluate the hygienic state of goat's milk, depending on the Total Bacteria Count and Total Fungi count. Milk samples were collected from each goat every ten days and for three times. The samples represented the fore-milk, remained milk [which is free from fore- milk] and the total milk. The laboratory examination of milk samples revealed that the total bacteria count were [3.36 log for fore - milk, 2.8 log for remained milk and 3.3X103log/ ml[cfu] for mixed milk]. Also total fungi count were[ 2.72 log for fore - milk, 2.5 log for remained milk and 2.63 X102 log / ml[cfu] for mixed milk ]. The results showed that there is variation in the percentage of total bacteria count and total fungi between the fore-milk, remained milk which free from fore- milk and the mixed milk were 72.25, 12. 88 , 68.28 % and 39.77, 18.74, 25.89% respectively.
Keywords: Goat milk Bacteria Fungi Foremilk Udder preparation Total bacterial count